Clinical features and follow-up in patients with 22q11.2 deletion syndrome. - Cancrini, Caterina; Puliafito, Pamela; Digilio, Maria Cristina; Soresina, Annarosa; Martino, Silvana; Rondelli, Roberto; Consolini, Rita; Ruga, Ezia Maria; Cardinale, Fabio; Finocchi, Andrea; Romiti, Maria Luisa; Martire, Baldassarre; et al. (J Pediatr, 2014)
OBJECTIVE: To investigate the clinical manifestations at diagnosis and during follow-up in patients with 22q11.2 deletion syndrome to better define the natural history of the disease. STUDY DESIGN: A retrospective and prospective multicenter study was conducted with 228 patients in the context of the Italian Network for Primary Immunodeficiencies. Clinical diagnosis was confirmed by cytogenetic or molecular analysis. RESULTS: The cohort consisted of 112 males and 116 females; median age at diagnosis was 4 months (range 0 to 36 years 10 months). The diagnosis was made before 2 years of age in 71% of patients, predominantly related to the presence of heart anomalies and neonatal hypocalcemia. In patients diagnosed after 2 years of age, clinical features such as speech and language impairment, developmental delay, minor cardiac defects, recurrent infections, and facial features were the main elements leading to diagnosis. During follow-up (available for 172 patients), the frequency of autoimmune manifestations (P = .015) and speech disorders (P = .002) increased. After a median follow-up of 43 months, the survival probability was 0.92 at 15 years from diagnosis. CONCLUSIONS: Our data show a delay in the diagnosis of 22q11.2 deletion syndrome with noncardiac symptoms. This study provides guidelines for pediatricians and specialists for early identification of cases that can be confirmed by genetic testing, which would permit the provision of appropriate clinical management.
Keywords: Abnormalities, Multiple; Adolescent; Adult; Age Factors; Child; Child, Preschool; Chromosomes, Human, Pair 22; Delayed Diagnosis; Developmental Disabilities; DiGeorge Syndrome; Disease Progression; Early Diagnosis; Female; Follow-Up Studies; Genetic Testing; Humans; Infant; Infant, Newborn; Male; Monitoring, Physiologic; Prospective Studies; Retrospective Studies; Risk Assessment; Severity of Illness Index; Sex Factors; Time Factors; Young Adult

Clinical heterogeneity and diagnostic delay of autoimmune polyendocrinopathy-candidiasis-ectodermal dystrophy syndrome. - Mazza, Cinzia; Buzi, Fabio; Ortolani, Federica; Vitali, Alberto; Notarangelo, Lucia D; Weber, Giovanna; Bacchetta, Rosa; Soresina, Annarosa; Lougaris, Vassilios; Greggio, Nella A; Taddio, Andrea; Pasic, Srdjan; et al. (Clin Immunol, 2011)
Autoimmune polyendocrinopathy-candidiasis-ectodermal dystrophy (APECED) is a rare autosomal recessive organ-specific autoimmune disorder that is characterized by a variable combination of (i) chronic mucocutaneous candidiasis, (ii) polyendocrinopathy and/or hepatitis and (iii) dystrophy of the dental enamel and nails. We analyzed the AIRE (autoimmune regulator) gene in subjects who presented any symptom that has been associated with APECED, including candidiasis and autoimmune endocrinopathy. We observed that 83.3% of patients presented at least two of the three typical manifestations of APECED, while the remaining 16.7% of patients showed other signs of the disease. Analysis of the genetic diagnosis of these subjects revealed that a considerable delay occurs in the majority of patients between the appearance of symptoms and the diagnosis. Overall, the mean diagnostic delay in our patients was 10.2 years. These results suggest that molecular analysis of AIRE should be performed in patients with relapsing mucocutaneous candidiasis for early identification of APECED.
Keywords: Adolescent; Adult; Child; Child, Preschool; Heterozygote; Homozygote; Humans; Middle Aged; Mutation; Polyendocrinopathies, Autoimmune; Time Factors; Young Adult

Forkhead box protein 3 (FOXP3) mutations lead to increased TH17 cell numbers and regulatory T-cell instability. - Passerini, Laura; Olek, Sven; Di Nunzio, Sara; Barzaghi, Federica; Hambleton, Sophie; Abinun, Mario; Tommasini, Alberto; Vignola, Silvia; Cipolli, Marco; Amendola, Mario; Naldini, Luigi; Guidi, Luisa; et al. (J Allergy Clin Immunol, 2011)
Keywords: Forkhead Transcription Factors; Gene Expression Regulation; Genetic Diseases, X-Linked; Humans; Immunologic Deficiency Syndromes; Intestinal Diseases; Male; Mutation; Polyendocrinopathies, Autoimmune

Functional type 1 regulatory T cells develop regardless of FOXP3 mutations in patients with IPEX syndrome. - Passerini, Laura; Di Nunzio, Sara; Gregori, Silvia; Gambineri, Eleonora; Cecconi, Massimiliano; Seidel, Markus G; Cazzola, Giantonio; Perroni, Lucia; Tommasini, Alberto; Vignola, Silvia; Guidi, Luisa; Roncarolo, Maria G; et al. (Eur J Immunol, 2011)
Mutations of forkhead box p3 (FOXP3), the master gene for naturally occurring regulatory T cells (nTregs), are responsible for the impaired function of nTregs, resulting in an autoimmune disease known as the immune dysregulation, polyendocrinopathy, enteropathy, X-linked (IPEX) syndrome. The relevance of other peripheral tolerance mechanisms, such as the presence and function of type 1 regulatory T (Tr1) cells, the major adaptive IL-10-producing Treg subset, in patients with IPEX syndrome remains to be clarified. FOXP3(mutated) Tr1-polarized cells, differentiated in vitro from CD4(+) T cells of four IPEX patients, were enriched in IL-10(+) IL-4(-) IFN-γ(+) T cells, a cytokine production profile specific for Tr1 cells, and expressed low levels of FOXP3 and high levels of Granzyme-B. IPEX Tr1 cells were hypoproliferative and suppressive, thus indicating that FOXP3 mutations did not impair their function. Furthermore, we isolated Tr1 cell clones from the peripheral blood of one FOXP3(null) patient, demonstrating that Tr1 cells are present in vivo and they can be expanded in vitro in the absence of WT FOXP3. Overall, our results (i) show that functional Tr1 cells differentiate independently of FOXP3, (ii) confirm that human Tr1 and nTregs are distinct T-cell lineages, and (iii) suggest that under favorable conditions Tr1 cells could exert regulatory functions in IPEX patients.
Keywords: Cell Differentiation; Cell Lineage; Cells, Cultured; Enteritis; Forkhead Transcription Factors; Genetic Diseases, X-Linked; Humans; Immunity, Innate; Interleukin-2 Receptor alpha Subunit; Mutation; Polyendocrinopathies, Autoimmune; Syndrome; T-Lymphocytes, Regulatory